Fiber-Optic Sensor Spectrum Noise Reduction Based on a Generative Adversarial Network - Yujie Lu; Qingbin Du; Ruijia Zhang; Bo Wang; Zigeng Liu; Qizhe Tang; Pan Dai; Xiangxiang Fan; Chun Huang (Sensors)
In the field of fiber-optic sensing, effectively reducing the noise of sensing spectra and achieving a high signal-to-noise ratio (SNR) has consistently been a focal point of research. This study proposes a deep-learning-based denoising method for fiber-optic sensors, which involves pre-processing the sensor spectrum into a 2D image and training with a cycle-consistent generative adversarial network (Cycle-GAN) model. The pre-trained algorithm demonstrates the ability to effectively denoise various spectrum types and noise profiles. This study evaluates the denoising performance of simulated spectra obtained from four different types of fiber-optic sensors: fiber Fabry–Perot interferometer (FPI), regular fiber Bragg grating (FBG), chirped FBG, and FBG pair. Compared to traditional denoising algorithms such as wavelet transform (WT) and empirical mode decomposition (EMD), the proposed method achieves an SNR improvement of up to <semantics>13.71 dB</semantics>, an RMSE that is up to three times smaller, and a minimum correlation coefficient (<semantics>R2</semantics>) of no less than 99.70% with the original high-SNR signals. Additionally, the proposed algorithm was tested for multimode noise reduction, demonstrating an excellent linearity in temperature response with a <semantics>R2</semantics> of 99.95% for its linear fitting and <semantics>99.74%</semantics> for the temperature response obtained from single-mode fiber sensors. The proposed denoising approach effectively reduces the impact of various noises from the sensing system, enhancing the practicality of fiber-optic sensing, especially for specialized fiber applications in research and industrial domains.